Preservation of Biological Diversity of Domestic Animals in Hungary - Bodó, Imre (Acta Agraria Debreceniensis, 2002)
Since the 1992 Rio de Janeiro UNO Congress domestic animals belong also officially to the genetic diversity of the world. Non commercial domestic animal breeds should be maintained for many cultural and technical reasons. Conservation and preservation of living beings is nowadays in the programme of many regional, national and international organizations. The preservation of domestic animals is possible in situ (at the original place and conditions) and ex situ (by cryogenic methods). There are three era in the history of preservation of domestic animals: the epoch of spontaneous maintenance, the period of sporadic national activities and the era of international programme. Some of the questions to be solved by scientific research: the principles of selection of the candidate populations for maintenance, the different degrees of endangeredness, the necessary population size to be subsidized, the problem of inbreeding, the best mating systems etc. In Hungary the maintenance of endangered domestic animal breeds is based upon the low. The following breeds are on the list of protected breeds: − the Hungarian Grey cattle, − the Lipizzan, Shagya, Nonius, Gidran, Furioso,Kisbér Halfbred, Murinsulaner and Hucul horses, − the Racka, Tsigai and Cikta sheep, − the Mangalitsa pig, − the Hungarian yellow, white, speckled and the Transsylvanian naked necked hen, − the Bronze Turkey, − the Frizzle Feathered goose. Hopefully in the near future the breeders of traditional domestic animal breeds will find the possible niches for their special products.